Metagenomic Diagnosis for a Culture-Negative Sample From a Patient With Severe Pneumonia by Nanopore and Next-Generation Sequencing - Wang, Kaiying; Li, Peihan; Lin, Yanfeng; Chen, Hongbin; Yang, Lang; Li, Jinhui; Zhang, Tingyan; Chen, Qichao; Li, Zhonghong; Du, Xinying; Zhou, Yusen; Li, Peng; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Rapid and accurate etiologic diagnosis accelerates targeted antimicrobial therapy. Metagenomic analysis has played a critical role in pathogen identification. In this study, we leveraged the advantages of both the MinION and BGISEQ-500 platforms to make a bacteriologic diagnosis from a culture-negative lung tissue sample from an immunocompromised patient with severe pneumonia. Real-time nanopore sequencing rapidly identified Klebsiella pneumoniae by an 823bp specific sequence within 1 minute. Genomic analysis further identified blaSHV12，blaKPC-2，blaTEM-1，blaCTX-M-65，and other resistance genes. The same sample was further sequenced on the BGISEQ-500 platform, which presented consistent results regarding the most top dominant pathogens and provided additional information of resistance gene. Revised antibiotic treatment was followed by the patient’s clinical recovery. Though sample preparation and the interpretation of final results still need to be improved further, metagenomic sequencing contributes to the accurate diagnosis of culture-negative infections and facilitates the rational antibiotic therapy.